RETRACTED: Environmental migration: Causes, varieties and features of migration processes - Dyakonova Sofya; Palchikov Ilya; Botienko Alena; Kildeeva Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001